Profuturo AFP: cambio organizacional impulsado por el plan estratégico de recursos humanos - Arbaiza Fermini, Lydia (2002)
This document explains about the improvement strategies carried out by the new management of Profuturo AFP based on a management quality plan applied with the purpose of leading the market obtaining greater growth profitability brand positioning and achieving the fidelity of its affiliates. This change in the organization is based on a system whose fundamental objective is the fulfillment of the goals and objectives established in the strategic planning of the organization through the development of the workers in the improvement of their performance and personal well-being offering tools of education training and staff satisfaction resulting in the improvement of the working environment.